Mogućnost primjene metode ’Monte Carlo’ u tehnologiji zračnog prometa - Radačić, Željko; Stanković, Ratko (Promet - Traffic&Transportation, 2012)
With respect to the characteristics of conventional methods for setting up the traffic/technological system in air transport and having in mind the very nature of these systems, the advantages of application of the Monte Carlo method have been discussed to create the possibilities for a different high-quality approach to the issue.